Let Students Talk about Emergency Remote Teaching Experience: Secondary Students' Perceptions on Their Experience during the COVID-19 Pandemic - Angelos Sofianidis; Maria Meletiou-Mavrotheris; Panagiota Konstantinou; Nayia Stylianidou; Konstantinos Katzis (MDPI AG, 2021)
This research aimed to comprehend the impact of the first school closure on secondary education in Cyprus from students' perspectives. Through the administration of an online survey with both closed and open questions, the study investigated the main issues and challenges that students experienced during their abrupt transition from face-to-face to emergency remote education and their main worries and concerns during this period, as well as their perceptions regarding the effectiveness of the teaching and learning process followed during the distance education period. The study also elicited students' suggestions, based on their experiences from the lockdown period, on improving instruction in case of further lockdown(s) and in the post-COVID-19 era. Three hundred twenty-two (322) students of both upper and lower secondary education participated in the study. The data from closed questions were analysed using descriptive and inferential statistics, and for the data from the open questions, a qualitative thematic analysis approach was followed. The valuable insights gained from this study illustrate how important it is for educators and educational policymakers to give voice to students, closely listen to what learners felt worked and what did not during the period of remote learning, and develop plans and policies that incorporate their feedback.